Avaliação diagnóstica sobre a gestão do conhecimento: um estudo realizado na Universidade Federal do Ceará (UFC) - Pereira, Anderson Silva (2022)
In a society in which transformations are increasingly accelerated, in which resources are increasingly scarce and the appreciation of intangible resources is increasingly evident, institutions find themselves in a challenging scenario and in constant movement. In this sense, knowledge management proves to be essential for the maintenance of 21st centusry organization. The Knowledge management is important for public administration, as it aims to promote the efficiency of public resources and the effectiveness of the services provided, especially in educational institutions, as they are institutions that deal directly with knowledge. The present study aims to diagnose knowledge management at the Federal University of Ceará from the perspective of its public servant. Regarding the methodological aspects, regarding the approach to the problem, it is a quantitative research; with regard to objectives, it is classified as descriptive; as for the technical procedures, it is characterized as a field survey. The research data were obtained through a questionnaire, made in google forms, and sent to all the institution's public servant, through a list of emails sent by the secretary of the Pro-rectory of people management. Therefore, despite the general average indicating a tendency to moderate classification, it is concluded, considering a systemic analysis of the set of results obtained, that the diagnosis of knowledge management at the Federal University of Ceará is tending to be weak. Regarding the comparison of the perception of teachers, TAEs, managers and non-managers, there was no difference in the classification of knowledge management.